EKONOMI KREATIF: BENTUK USAHA PENINGKATKAN PENDAPATAN MASYARAKAT DALAM PERSPEKTIF EKONOMI SYARIAH DI KEMAYORAN BANGKALAN - Buhari, A. Taufiq (Jurnal Istiqro, 2025)
This study discusses the development of a creative economy based on organic waste management in Kemayoran Village, Bangkalan, through TPS3R Rengkes Onggu. The creative economy is understood as a concept that integrates creativity, knowledge, and information to promote sustainable development, with creativity, invention, and innovation as its main pillars. Factors such as education, skills, experience, age, risk-taking ability, capital/inheritance, market conditions, and discrimination influence income levels. Waste management activities involve collection, sorting, shredding, fermentation using EM4, periodic stirring, grinding, and packaging into 3 kg compost bags. As a result, marketing that was initially limited has now expanded, enabling the production of 0.5–1 ton of compost per month with a turnover of approximately IDR 2,000,000 per sale, although challenges remain in maintaining income stability and management efficiency